Монголчуудын нүүдэллэлт, шалтгаан, сургамж - Чулуунбаатар, Лувсандоо (Historia Mongolarum, 2003)
From the ancient times the Mongols migration traditionally were dependant on the weather condition impact and the requirements of livestock breeding. Also the political factors, such as conflict and struggle among many tribes, had an influence on this process. The migration everlasting process and also one of the basic factors of humanity. It is important to study nomadism from new and updated concepts.